The repair of chipped ceramics with the direct adhesive technique of self-adhesive system for fixing on a composite basis BIFIX SE (VOCO, Germany). The clinical case - Symonenko Р. В. (Actual Dentistry, 2021)
The single chips of ceramic structures remain a big problem for both the patient and for the doctor, especially in the frontal area, when for some objective reason, they cannot immediately change the construction. The work is justified by the choice of materials and the method of direct restoration of a single defect is described on a zirconium basis using the BIFIX SE self-adhesive system and the Futurabond U universal adhesive (VOCO, Germany). The repair of chipped ceramics is a real necessity. And the durability of restorations directly depends on the compliance with adhesive work technique, as well as the analysis of the reasons leading to the destruction of the ceramic mass and following up the patient’s regime.